Heterocyclic Compounds as Hsp90 Inhibitors: A Perspective on Anticancer Applications - Mina Ardestani; Zahra Khorsandi; Fariba Keshavarzipour; Siavash Iravani; Hojjat Sadeghi-Aliabadi; Rajender S. Varma (MDPI AG, 2022)
Heat shock proteins (Hsps) have garnered special attention in cancer therapy as molecular chaperones with regulatory/mediatory effects on folding, maintenance/stability, maturation, and conformation of proteins as well as their effects on prevention of protein aggregation. Hsp90 ensures the stability of various client proteins needed for the growth of cells or the survival of tumor cells; therefore, they are overexpressed in tumor cells and play key roles in carcinogenesis. Accordingly, Hsp90 inhibitors are recognized as attractive therapeutic agents for investigations pertaining to tumor suppression. Natural Hsp90 inhibitors comprising geldanamycin (GM), reclaimed analogs of GM including 17-AAG and DMAG, and radicicol, a natural macrocyclic antifungal, are among the first potent Hsp90 inhibitors. Herein, recently synthesized heterocyclic compounds recognized as potent Hsp90 inhibitors are reviewed along with the anticancer effects of heterocyclic compounds, comprising purine, pyrazole, triazine, quinolines, coumarin, and isoxazoles molecules.